Fritz von Unruh - ein Tolstojaner? - Orłowski, Hubert (Studia Germanica Posnaniensia, 2018)
The text "Fritz von Unruh - the follower of Tolstoy's view" deals with the views, attitude and political activities of an eminent writer Fritz von Unruh who came from the well-known family of Prussian junkers who served for many generations the Prussian kings and the Wilhelm Reich. His experiences of the I World War brought about a distinct change in the writer's attitude, namely, he turned toward pacifism and antimilitarism. Thesis of the work proclaims: von Unruh was under the influence of Leo Tolstoy's views, which by necessity must have led to misunderstanding of the principle obligatory for each writer-politician. Namely, to want, to desire - is one thing, whereas to be able to is another thing. Not differentiating between "the spirit" and "act" (cf. Max Weber) must have ended with the inefficiency of actions of the writer von Unruh - the actions of a distinct moral option.